Small-Scale Farmers’ Uptake of Eco-Friendly Vegetable Production Practices in Enugu State, Nigeria. - Ikenna Charles Ukwuaba; Chiziterem Benita Nze; Ridwan Mukaila; Sunday Ifeanyi Ukwuaba; Chukwuma Otum Ume; Emmanuel Ejiofor Omeje; Ogochukwu Gabriella Onah; Chris Nnamdi Onyekwe; Onyebuchi Jonathan Umeh (Journal of Agricultural Extension)
The rising demand for sustainable agriculture is driving a global shift toward eco-friendly vegetable production methods that prioritise human health and environmental protection Vegetables. however, the level of uptake of eco-friendly practices and their drivers are poorly understood, which prompts the current study. A semi-structured questionnaire was used to collect data from 300 randomly selected vegetable farmers in Enugu State. Descriptive statistics and multinomial logistic regression were used for data analysis. Results show that standard eco-friendly practices adopted by vegetable farmers included minimum/no tillage (87.0%), intercropping (64.0%), reduction of chemical inputs (64.0%), agroforestry (46%), and organic farming (33%). Most (71%) farmers were medium-level adopters of eco-friendly practices. The primary constraints to the uptake of eco-friendly practices included limited access to resources (????? =4.50), limited technical knowledge (????? =4.04) and lack of support from research and extension services (????? =4.03). Education (p<0.1), farm size (p<0.05), farming experience (p<0.05), consumer demand (p<0.05), and access to credit (p<0.05) were the socioeconomic and institutional factors that influenced the level of adoption of eco-friendly vegetable production practices. To accelerate the transition to sustainable farming, the study recommends innovative solutions such as tailored farmer education programs, microfinance initiatives, government subsidies, and robust research-extension linkages.